Identification of Potential Processed Products from Coconut Water for MSME Development in Indonesia - Mela, Ervina; Mustaufik, Mustaufik; Budiarti, Laeli; Elza, Livianinda (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
Coconut products, especially coconut water, have the potential to be carried out on a household or MSME scale. The purpose of this study was to identify processed products from coconut water that have the potential to be developed on an MSME scale in Indonesia. The study was conducted in 2 stages. The first stage is the identification of processed products from coconut water. The second stage is the selection of potential products. The selection of potential products was done by applying the Bayes method through interviews with 9 experts. The selection criteria were market potential, business capital, technology, human resources and and availability of raw materials. The study results showed that the products in the top 3 rankings were nata de coco, coconut vinegar, and packaged coconut water. The study results are expected to be useful for related stakeholders such as MSMEs, local governments, and universities to develop downstream coconut water products.